The Role of Vocational High Schools in Increasing Graduate Absorption in the Cities of Depok and Bogor - Pramono, Danan Wuryanto; Hadiyati, Ernani; Purnomo, Eko Priyo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This research aims to identify the steps that have been taken by SMK Forward Nusantara in order to improve and build the school's image as shown by the absorption of graduates. This research was designed with a qualitative approach and used interview, observation and document analysis research instruments. The results of this research state that SMK Forward Nusantara has a mission to create a mid-level workforce that is skilled and professional and ready to enter the world of work/industry and is expected to be able to channel its alumni or act as job introducers. This hope can be realized by entering into a cooperation agreement between the Employment Service, the Education Service and the Business/Industrial World which is linear with the existing departments. As a follow-up to the cooperation agreement, SMK Forward Nusantara is responsible for absorbing its graduates to obtain jobs that suit their interests, abilities and career by establishing a Special Job Fair.